INTELLECTUAL PROPERTY RIGHTS REGARDING LEGAL CERTAINTY OF BEAUTY CLINIC PRODUCT LOGO BRAND - Muhammad Rifzal Alief Ramadhan; Azhar Rashed; Adiatama Wira Buana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the judge's considerations and legal consequences of the cancellation of registered trademarks and determine the party who has the right to be the actual holder of trademark rights to the issuance of intellectual property rights trademarks and product logos. Law Number 20 of 2016 concerning Trademarks and Geographical Indications states that registered trademark owners can file a lawsuit against other parties who without the right to use the Trademark that has similarities in principle or all for similar goods and/or services by filing a lawsuit for compensation and/or termination of acts related to the use of the Trademark. With this article, it can benefit registered trademark owners to be able to file a lawsuit against parties who try to piggyback on their brands to make profits. The problem is that the use of trademarks that contain similarities is basically proven to violate the provisions of Article 21 paragraph 1 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications, showing that trademark law enforcement in Indonesia has not been carried out effectively that the theory of legal effectiveness according to Soekanto which states that the effectiveness of law enforcement can be influenced by certain factors, including legal factors, law enforcement factors, community factors, and cultural factors. In conclusion, the Judge has an important role in deciding the Trademark dispute case because it is to interpret the law so that it is possible for the judge to find legal value and even create a legal rule as contained in case law. These reasons or arguments are intended as the judge's accountability rather than his decision to the community, so that therefore they have objective value.